2019
DOI: 10.1002/ajp.22986
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of gut microbiomes in captive nocturnal strepsirrhines

Abstract: Feeding strategy and diet are increasingly recognized for their roles in governing primate gut microbiome (GMB) composition. Whereas feeding strategy reflects evolutionary adaptations to a host's environment, diet is a more proximate measure of food intake. Host phylogeny, which is intertwined with feeding strategy, is an additional, and often confounding factor that shapes GMBs across host lineages.Nocturnal strepsirrhines are an intriguing and underutilized group in which to examine the links between these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Furthermore, due to the advent of modern sequencing technologies, significant research effort has been aimed at disclosing the microbiota composition of non‐human primates and at investigating how this is influenced by ecological variation through time (Greene et al ., 2019; Orkin et al ., 2019). These studies described gut mirobiomes of several non‐human primate species in which Actinobacteria were outnumbered by Firmicutes and Bacteroidetes, being reminiscent of the human gut microbiota (Bornbusch et al ., 2019; Gomez et al ., 2019; Greene et al ., 2019). In contrast, reports on the gut microbiota of members of the Cebidae family highlighted a bacterial composition dominated by the genera Streptococcus and Bifidobacterium (Orkin et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the advent of modern sequencing technologies, significant research effort has been aimed at disclosing the microbiota composition of non‐human primates and at investigating how this is influenced by ecological variation through time (Greene et al ., 2019; Orkin et al ., 2019). These studies described gut mirobiomes of several non‐human primate species in which Actinobacteria were outnumbered by Firmicutes and Bacteroidetes, being reminiscent of the human gut microbiota (Bornbusch et al ., 2019; Gomez et al ., 2019; Greene et al ., 2019). In contrast, reports on the gut microbiota of members of the Cebidae family highlighted a bacterial composition dominated by the genera Streptococcus and Bifidobacterium (Orkin et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteroides -two, closely related taxa with similar functional potential 71 -dominated the observed relationships. The strength and quantity of relationships between Bacteroides and other bacterial taxa support the foundational membership of Bacteroides in the lemur gut microbiome 42,72,73 . Notably, increases in the log ratio abundance of Bacteroides during antibiotic treatment indicated that its members maintained or increased their relative abundances while other taxa were eliminated.…”
Section: Of the Bacterial Associations Present In The Two Treatment Cmentioning
confidence: 79%
“…The increased similarity was evidenced in both the presence-absence and the abundance-weighted metrics of phylogenetic compositions (i.e., unweighted and weighted UniFrac), indicating that both rare and abundant microbes were driving the pattern of rewilding. We thus explored specific patterns in Bacteroides, Prevotella, and Ruminococcus-three dominant members of primate GMBs 8,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%